Dampak Work Related Stress Terhadap Kinerja Tenaga Pemasaran - Rizky Praditiya Herdiana; Maya Setiawardhani (Jurnal Riset Bisnis dan Investasi, 2020)
Human resources is one important aspect to run the company activities. The company needs to manage their human resources to achieve optimal results. Managing employee’s work stress may impact optimal employee performance. This study aim to find out the impact work related stress on employee performance account executive in PT Agrodana Futures Bandung. This research used deskriptive quantitative method. Based on research on 110 respondents, the results show that there is an impact from work related stress on employee performance. The regression analysis showing the results Y=6,120+0,478X. This shows that if the work related stress increases one, then it will add employee’s performance equal to 0,478 and work related stress influnced 64,2% employee performance and the rest is influenced by other. Although the performance of account executive employees of PT Agrodana Futures Bandung is high, but the company can still improve their performance to the best.